Implementasi Blended Learning untuk Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam di Masa Pandemi Covid-19 - Faizatin, Anis (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2021)
The aims of this study were to (1) describe the design of blended learning in improving the quality of PAI learning during the pandemic at MI Al Usman; (2) describe the implementation of blended learning in improving the quality of PAI learning during the pandemic at MI Al Usman; and (3) describe the impact of applying blended learning in improving the quality of PAI learning during the pandemic at MI Al Usman. This research was conducted using a qualitative approach with the type of case study. Data were collected through observation, interviews, and documentation. The application of blended learning at MI Al Usman brings many positive impacts, especially for students and for all stakeholders compared to fully online learning, which is felt to be less effective because there is no face-to-face interaction between educators and students, especially in Islamic Education subjects, which in some of its materials requires direct practice.